Measurement of normal optic nerve head parameters - Samarawickrama, Chameen; Jonas, Jost B. (Survey of ophthalmology, 2012)
All optic nerve pathologies, including the glaucomas and disorders such as non-arteritic ischemic optic neuropathy, affect the appearance of the optic nerve head. Morphological examination of the optic nerve head in a qualitative and quantitative manner is therefore clinically mandatory. With the advent of modern imaging modalities such as confocal scanning laser tomography and optical coherence tomography, new diagnostic avenues have opened up to further refine the examination. The new imaging devices are now becoming a major adjunct to the diagnosis and long-term management of optic nerve head pathology; before it is possible to identify an abnormal optic disk, however, it is essential to understand the morphology and measurement of the normal disk. We summarize recent data on the normal morphology and measurement of optic nerve head parameters as assessed by the major imaging modalities now available.
Available online 20 June 2012
Gesehen am 26.06.2018